Size‐selective purification of hepatitis B virus‐like particle in flow‐through chromatography: Types of ion exchange adsorbent and grafted polymer architecture. Issue 10 (15th March 2018) - Ng, Hon Wei; Lee, Micky Fu Xiang; Chua, Gek Kee; Gan, Bee Koon; Tan, Wen Siang; Ooi, Chien Wei; Tang, Siah Ying; Chan, Eng Seng; Tey, Beng Ti
Abstract: Hepatitis B virus‐like particles expressed in Escherichia coli were purified using anion exchange adsorbents grafted with polymer poly(oligo(ethylene glycol) methacrylate) in flow‐through chromatography mode. The virus‐like particles were selectively excluded, while the relatively smaller sized host cell proteins were absorbed. The exclusion of virus‐like particles was governed by the accessibility of binding sites (the size of adsorbents and the charge of grafted dextran chains) as well as the architecture (branch‐chain length) of the grafted polymer. The branch‐chain length of grafted polymer was altered by changing the type of monomers used. The larger adsorbent (90 μm) had an approximately twofold increase in the flow‐through recovery, as compared to the smaller adsorbent (30 μm). Generally, polymer‐grafted adsorbents improved the exclusion of the virus‐like particles. Overall, the middle branch‐chain length polymer grafted on larger adsorbent showed optimal performance at 92% flow‐through recovery with a purification factor of 1.53. A comparative study between the adsorbent with dextran grafts and the polymer‐grafted adsorbent showed that a better exclusion of virus‐like particles was achieved with the absorbent grafted with inert polymer. The grafted polymer was also shown to reduce strong interaction between binding sites and virus‐like particles, which preserved the particles' structure.